Optimizing induction chemotherapy regimens for radiotherapy in patients with locoregionally advanced nasopharyngeal carcinoma - Ying Li; Jianping Bi; Guoliang Pi; Hanping He; Yanping Li; Dandan Zheng; Zecheng Wei; Guang Han (Cancer Medicine, 2023)
Abstract Background and Purpose The optimal number of cycles of induction chemotherapy (IC) in locoregionally advanced nasopharyngeal carcinoma (LANPC) remains unresolved. This study aimed to quantitatively assess the changes in gross tumor volumes (GTVs) and to select the most optimal number of IC cycles. Methods We analyzed 54 patients who received a three‐cycle IC before commencing radiotherapy, with the tumor and nodal responses assessed by a CT scan before IC and after each IC cycle. The gross tumor volumes of the nasopharynx primary lesion (GTV_T), involved retropharyngeal lymph node (GTV_RP), and involved cervical lymph node (GTV_N) were contoured on each scan. The volume change following each IC cycle was evaluated with Wilcoxon signed‐rank test. The three‐dimensional vector displacements of target centers were also calculated and compared. Results The volume reductions of GTVs following IC varied across different patients and showed different trends for the three GTV types. GTV_T and GTV_RP did not display further volume reduction after two IC cycles, whereas GTV_N showed monotonic volume decreases. For GTV_T and GTV_RP following the three IC cycles, the total volume reduction relative to the initial volume before IC was 12.0%, 22.5%, and 20.1% and 26.0%, 44.1%, and 42.2%, respectively. In contrast, for GTV_N, continuing volume reduction was observed with a total reduction of 25.3%, 43.2%, and 54.7% following the three cycles, and the reductions were all significant. Average displacements of the GTVs were <1.5 mm in all directions; their average three‐dimensional displacements were 2.6, 4.0, and 1.7 mm, respectively. Acceptable toxicity was observed in most patients. Conclusion This study supports two cycles of IC before radiotherapy for patients with LANPC if the initial metastatic cervical lymph node volume is not dominating. Otherwise, three cycles of IC is recommended to further reduce the cervical node volume.